THE EFFECT OF PRODUCT QUALITY, BRAND IMAGE AND TASTE ON THE PURCHASE DECISION OF KUDA CAP TENGGIRI FISH CRACKERS SEA IN BANGKOK CITY - Desi Eka Pratiwi; Mohd. Heikal; Jullimursyida; Hamdiah (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The increasingly tight competition among processed seafood products requires every producer to keep innovating in order to compete with its rivals. Product quality, brand image, and taste are important factors that producers need to pay attention to in order to maintain and improve consumer purchasing decisions. Pre-survey results on Cap Kuda Laut Mackerel Fish Crackers show a declining trend in consumer purchase interest, which is suspected to be related to these three factors. This study aims to determine the influence of Product Quality (X1), Brand Image (X2), and Taste (X3) on Purchasing Decisions (Y) of Cap Kuda Laut Mackerel Fish Crackers in Pangkalan Brandan, Langkat Regency, North Sumatra. The population of this study consists of consumers of the product. The sample consisted of 100 respondents, determined using the purposive sampling technique. The variables in this study consist of dependent and independent variables. The dependent variable is Purchasing Decision (Y), while the independent variables are Product Quality (X1), Brand Image (X2), and Taste (X3). The method used in this study is a quantitative research method, with multiple linear regression as the analysis model. Data processing was carried out using the SPSS program. Based on the analysis results, this study found that the Product Quality variable has a positive and significant effect on Purchasing Decision, Brand Image has a positive and significant effect on Purchasing Decision, and the Taste variable has a positive and significant effect on Purchasing Decision. The results of this study also show that Product Quality, Brand Image, and Taste have a partial and simultaneous effect on the Purchasing Decision of Cap Kuda Laut Mackerel Fish Crackers.